Self-physical and emotional perception in water polo for drop out - Viscione, I.; Invernizzi, P. L.; Ferrara, F. (Journal of Human Sport & Exercise, 2019)
To try to have a global view of the phenomenon of abandonment, we must ask ourselves what are the main reasons and psychological dynamics that convince a child to start any sport activity. In Italy, unfortunately, it is not always the children who choose the physical and sporting activity to practice, but often it is the parents and this is a serious mistake and could be one of the causes of abandonment at an early age. Sport activity in adolescence, especially practiced at a competitive level, is grafted on ground rich in interpersonal reversals and existential problems, going to affect intrapsychic dynamism and acting on the ability to control the ego and the unconscious dynamics that in this period undergo massive readjustments. The aim of the study is to study, in different groups of athletes (7-12 years, 13-17 years, 17-30 years) of water polo, how they deal emotionally and physically with the physical and emotional workloads and especially if you find physical and mental well-being. The method of the study is qualitative/quantitative and the administration of 10 questions: 5 to identify the physical self-perception and 5 for the emotional one, is done anonymously. The data shows that the self-perception for physical performance is on average positive and the self-perception for motivation performance is on average negative. This data is significant for the perceptive state of the athletes to whom it is necessary to refer in order to face the problem realistically. Given the data and their significance, the study must be deepened with a more significant and detailed sample of data.